Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/adma.201501130
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Uniform Fe3O4 Hollow Spheres Organized by Ultrathin Nanosheets and Their Excellent Lithium Storage Properties

Abstract: Hierarchical Fe3 O4 hollow spheres constructed by nanosheets are obtained from solvothermally synthesized Fe-glycerate hollow spheres. With the unique structural features, these hierarchical Fe3 O4 hollow spheres exhibit excellent electrochemical lithium-storage performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
218
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(227 citation statements)
references
References 55 publications
(72 reference statements)
8
218
1
Order By: Relevance
“…Recent researches have demonstrated that hollow spheres constructed with 1D nanorods/nanoneedles18 and 2D nanosheets19, 20, 21, 22 even exhibit faster surface reaction rates and better physicochemical stability because they occupy much larger specific surface areas than the most hollow spheres composed of 0D nanoparticles,23 and simultaneously inherit the characteristics of the constituent units. However, synthesis of this kind of hierarchical hollow structures is generally challenging due to the difference of stability between core and shell materials 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have demonstrated that hollow spheres constructed with 1D nanorods/nanoneedles18 and 2D nanosheets19, 20, 21, 22 even exhibit faster surface reaction rates and better physicochemical stability because they occupy much larger specific surface areas than the most hollow spheres composed of 0D nanoparticles,23 and simultaneously inherit the characteristics of the constituent units. However, synthesis of this kind of hierarchical hollow structures is generally challenging due to the difference of stability between core and shell materials 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…31 The detailed procedures are as follows. Firstly, 0.5 mmol of Fe(NO3)3·9H2O and 7.5 mL of glycerol were added into a 100-mL Teflon container pre-filled with 52.5 mL of isopropanol.…”
Section: Preparation Of Fe3o4 Hollow Nanospheres and Fe3o4 Nanoparticlesmentioning
confidence: 99%
“…[153][154][155][156][157][158][159][160][161] As a typical example, Lou et al prepared uniform Fe3O4 hierarchical hollow spheres comprised of nanoplate building blocks (Figures 9a and 9b) by an ethylene glycol-mediated solvothermal method. [159] The product delivered a reversible capacity of 640 mAh·g -1 at 200 mA·g -1 , retaining 580 mAh·g -1 after 100 cycles (Figure 9c).…”
Section: Fe3o4-based 3d Nanostructuresmentioning
confidence: 99%
“…In another study, the same group synthesized monodisperse Fe3O4 hollow spheres organized by ultrathin nanosheets (Figures 9d and 9e), which demonstrated a high reversible capacity of 1046 mAh·g -1 without noticeable capacity fading over 100 cycles. [160] [159] SEM images (d, e) and rate performance (f) of Fe3O4 hierarchical hollow spheres constructed by ultrathin nanosheets. [160] With desirable free spaces for volume change accommodation, yolk@shell structures have also been fabricated to boost the electrochemical performances of Fe3O4.…”
Section: Fe3o4-based 3d Nanostructuresmentioning
confidence: 99%